Youth protection law in Québec - Provost, Mario (LexisNexis Canada, 2023)
"This handbook presents youth protection law in Quebec. Practitioners, workers from the DYP, and anyone wishing to broaden their knowledge on the various legal aspects of this area of practice will greatly benefit from this helpful guide. It is a translation of the highly successful French publication, Droit de la protection de la jeunesse, 3e édition, written by the same author."– Provided by publisher.